Acute toxicity and synergistic and antagonistic effects of the aromatic compounds of some essential oils against Culex quinquefasciatus Say larvae - Pavela, Roman (Parasitology research, 2015)
The efficacy of 30 aromatic compounds and their mutual binary combinations was assessed for acute toxicity against the larvae Culex quinquefasciatus. Based on comparison of the lethal doses, thymol and p-cymene were selected as the most effective (LD50 = 18 and 21 mg L(-1), respectively, and LD90 = 25 and 30 mg L(-1), respectively). Although the LD50 for terpinolene and trans-anethole was also estimated at 21 mg L(-1), their LD90 was significantly higher compared to the substances above (245 and 34 mg L(-1), respectively). In total, 435 binary combinations were tested, of which 249 combinations showed a significant synergistic effect, while 74 combinations showed a significant antagonistic effect on mortality. Only nine substances were identified as being able to create a synergistic effect with more than 20 substances: limonene, trans-anethole, 4-allylanisole, carvacrol, isoeugenol, menthone, carvone, borneol, and camphor. The highest synergistic effect on larval mortality was achieved for the combinations: eugenol and isoeugenol, carvone and carvacrol, carvone and 4-allylanisole, carvone and α-terpineol, carvone and menthone, limonene and trans-anethole, limonene and menthone, α-pinene and menthone, β-citronellol and menthone, carvacrol and 4-allylanisole, carvacrol and terpineol, α-terpinene and trans-anethole, camphor and menthone, camphene and menthone, and 4-allylanisole and menthone. Significant differences between achieved mortality and the mutual mixing ratio were found for the five selected binary mixtures that had shown the most significant synergistic effect in the previous tests. The mixture of limonene and trans-anethole showed the highest mortality, with the mixing ratio 1:1; the mixture of eugenol and isoeugenol caused 90.2% mortality, with the mixing ratio 1:3. One hundred percent mortality was achieved if carvacrol was contained in a mixture with carvone in a ratio >2. After a comparison of all our results, based on our experiments, we can choose two pairs that caused mortality higher than 90% in concentrations lower than 20 mg L(-1): limonene and trans-anethole (with the mixing ratio 1:1), and carvone and carvacrol (with the mixing ratio 1:2-3). The information gained can thus be used in the development of new botanical insecticides based on essential oils (EOs) and particularly in the creation of formulations.
Keywords: Oils, Volatile; larva; Larva; lékové interakce; Drug Interactions; Insecticides; synergismus léků; Drug Synergism; Animals; zvířata; insekticidy; oleje prchavé; Culex